Metal accumulation in House Sparrow (Passer domesticus) from Thohoyandou, Limpopo province, South Africa. Issue 1 (2nd January 2017) - Baker, Nathan J; Dahms, Simone; Gerber, Ruan; Maina, John; Greenfield, Richard
Abstract : Studies on metal pollution (cadmium, cobalt, chromium, copper, manganese and nickel) in South African terrestrial environments are severely lacking. Due to being relatively unaffected by industrialisation, the Thohoyandou region may provide data on natural levels of metals for use as baseline data. The House Sparrow ( Passer domesticus ) was chosen as a bio-indicator of metal pollution due to its abundance, non-migratory lifestyle and close association with humans. The aims were to determine the viability of using feathers as a non-lethal bio-indicator tissue compared with muscle. Plume feathers, flight feathers and muscle tissue were analysed using ICP-OES techniques. Analyses of tissue metal concentrations identified the following trend: plume feather > flight feather > muscle tissue. Within the Thohoyandou region, Magondi, which was affected by anthropogenic activities at the time of sampling, had significantly higher concentrations ( p ≤ 0.05) for each of the metals, indicating potential metal contamination from various sources. Alternatively, Makonde had the lowest metal concentrations and may be an important reference site for future comparative studies. The results showed that the House Sparrow can be used as a bio-indicator organism in South African terrestrial environments. The plume feathers indicate that they are a good non-lethal tissue for determining metal pollution levels on a temporal scale, indicating recent metal exposure.